Development of quantification methods of a new selective carbonic anhydrase II inhibitor in plasma and blood and study of the pharmacokinetics of its ophthalmic suspension in rats - Alexander L. Khokhlov; Ilya I. Yaichkov; Mikhail K. Korsakov; Anton A. Shetnev; Nikita N. Volkhin; Sergey S. Petukhov (Belgorod National Research University, 2023)
Introduction: Development of new bioanalytical methods is required for studying the systemic exposure of new selective inhibitor of carbonic anhydrase II, 4-(2-methyl-1,3-oxazole-5-yl)-benzenesulfonamide, and its N-hydroxymetabolite in plasma and in whole blood. The results of the experiment with a single administration of an ophthalmic suspension of the drug are necessary to optimize the subsequent design of a full pharmacokinetic study. Materials and Methods: HPLC-MS/MS method was used to measure a concentration of analytes in plasma and whole blood. Chromatographic separation was performed on the Poroshell 120EC-C18 column (50*3.0 mm, 2.7 µm). Pharmacokinetics was studied on 6 Wistar rats weighing 287.50±18.64 g (Mean±SD). Each animal was instilled with 40 µL of the ophthalmic suspension in concentration of 2% in each eye. Blood samples were collected before administration of the drug and 30 min, 1 h, 1 h 30 min, 2 h, 3 h, 4 h, 6 h, 8 h, 12 h, 24 h, 48 h, and 72 h after administration. Non-compartment approach was used for the evaluation of pharmacokinetic parameters. Results and Discussion: The protein precipitation was chosen for a sample preparation of biological fluids. A solution of ascorbic acid in concentration of 10% was added to plasma, and a solution of sodium thiosulfate in concentration of 10% was added to blood to prevent the degradation of N-hydroxymetabolite of the drug. The analytical range of determination of 4-(2-methyl-1,3-oxazole-5-yl)-benzenesulfonamide and its N-hydroxyderivative in blood was 50-10000 ng/mL and 5-1000 ng/mL, respectively, in plasma - 10-2000 ng/mL and 1-200 ng/mL, respectively. The maximum plasma concentration of the studied drug was 264.32±68.47 ng/mL (Mean±SD) 1.92±0.92 h (Mean±SD) after administration, and its metabolite was 10.43±1.79 ng/mL 2.17±1.13 h after administration. The maximum concentration of the drug in blood reached 8705.23±1301.84 ng/mL (Mean±SD) 1.17±0.52 h (Mean±SD) after administration, and the maximum concentration of N-hydroxymetabolite reached 230.00±69.54 ng/mL (Mean±SD) 1.33±0.41 h (Mean± SD) after administration. Conclusion: The developed methods have been fully validated according to the requirements of Russian and internatonal guidelines and have been successfully used for pharmacokinetic research. It was found that a content of 4-(2-methyl-1,3-oxazole-5-yl)-benzenesulfonamide and its main metabolite in whole blood is significantly higher than in plasma.